Prognostic significance of microcalcifications in breast cancer (literature review) - V. O. Aksenenko; I. G. Frolova; E. Yu. Garbukov; E. G. Grigoryev; M. P. Ramazanova; E. A. Usynin; S. V. Vtorushin; N. A. Alaichiev (Сибирский онкологический журнал)
Abstract. Breast cancer is one of the most commonly diagnosed cancers worldwide. According to the World Health Organization, the incidence of breast cancer was 2.26 million in 2020, overtaking the incidence of lung cancer. In Russian Federation, the increase in new cases of breast cancer over the ten years from 2005 to 2015 was 31.76 %. Microscopic calcium deposits within breast tissue, microcalcifications, can be early signs of breast cancer. Being a significant diagnostic finding, microcalcifications allow the assessment of the extent of the disease. A detailed understanding of the morphogenesis of microcalcifications can improve knowledge about early stages of breast cancer, but there is no studies that would combine the results of the latest basic scientific research and current knowledge about their clinical significance.The aim of the study was to analyze and summarize the available data on the prognostic value of microcalcifications in patients with breast cancer.Material and Methods. A search was carried out for available literary sources published in the Medline, Elibrary, etc. databases for the period since 2015. A total of 250 sources devoted to the analysis of the morphogenesis of microcalcifications and their diagnostic value were found. Of them, 37 were included in this review.